Oscillations of a hollow piezoceramic cylinder excited by a system of surface electrodes - Bardzokas, D. I.; Filshtinsky, M. L.; Rodriguez-Ramos, R.; Sanchez-Casals, O. (Computer Assisted Methods in Engineering and Science, 2002)
An antiplane mixed boundary problem of electro elasticity for a hollow piezoelectric cylinder with an arbitrary system of active surface electrodes exciting its oscillations is considered. The solution is carried out on the basis of the approach developed in [4] for investigation of the oscillations of a solid piezoceramic cylinder with a given system of active surface electrodes. Results of numerical realization of the obtained algorithm characterizing amplitude-frequency features of the cylinder and also the behaviour of electro elastic quantities in the cylinder area and on the boundary are given.